Justifying the Epistemological Theory of Argumentation: On Harvey Siegel’s Approach - Lumer, Christoph (Informal Logic, 2023)
This article discusses Harvey Siegel’s general justification of the epistemological theory of argumentation in his seminal essay “Arguing with Arguments." On the one hand, the achievements of this essay are honoured—in particular, a thorough differentiation of the different meanings of ‘argument’ and ‘argumentation,’ the semantic justification of the fundamentality of arguments as sequences of propositions, and the detailed critiques of alternative theories of argumentation. On the other hand, suggestions for strengthening the theory are added to Siegel's expositions, which make different perspectives within the epistemological theory of argumentation recognisable.